HISTORY OF DEVELOPMENT OF MARINE GEOLOGY AT NOVOROSSIYSK UNIVERSITY (1865-1920 GG.) - POLOVKA, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Article is devoted to formation and development of marine geological research in Novorossiysk (today ONU Mechnikov) University (1865 – 1920). Highlight the main results of the healthy lifestyle in the area and the Black Sea, focusing on theoretical and applied scientific achievements of the University in the field of geology of the oceans and seas.